Burning mouth syndrome: Clinical dilemma? - Kanchan R Patil; R S Sathawane (Wolters Kluwer Medknow Publications, 2008)
Burning Mouth Syndrome (BMS) is a chronic orofacial burning pain condition usually in the absence of clinical and laboratory findings that affects many adults worldwide, yet its etiology and treatment remain poorly understood. Though it has been associated with numerous oral and systemic conditions, there has been no clear consensus on its etiology, pathogenesis and treatment. As a result, patients with inexplicable oral complaints are often referred from one health care professional to another without effective management having significant emotional impact on patients. As the dental profession expands its scope of care to oral medicine and geriatrics, BMS will be more effectively diagnosed and managed by these dental surgeons. Hence, they should be more involved in evaluation and management of these patients. The present article provides updated information on BMS including possible etiological factors and current treatment options, although data on the effectiveness of these treatment modalities remain limited. Recently researchers found that treatment with a familiar nutritional supplement- lipoic acid- is of remarkable benefit with minimal adverse effects. ALA (alpha-lipoic acid) may be the effective treatment modality in management of BMS.